Transgender Intimate Partner Violence and Help-Seeking Patterns - Kurdyla, Victoria (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) against transgender individuals is highly prevalent and impactful, and thus research is needed to examine the extent to which survivors are able to reach needed assistance and safety. To our knowledge, no U.S.-based quantitative studies have explored transgender utilization patterns and perceptions regarding a broad range of help-giving resources (HGRs). The present article fills this gap in the literature by exploring help-seeking attitudes and behaviors of a convenience sample of 92 transgender adults and 325 cisgender sexual minority adults in the United States. Results from an online questionnaire indicate that, among the subsample experiencing IPV (n = 187), help-seeking rates were significantly higher among transgender survivors (84.1%) than cisgender sexual minority survivors (67.1%). In addition, transgender survivors most commonly sought help from friends (76.7%), followed by mental health care providers (39.5%) and family (30.2%), whereas formal HGRs such as police, IPV telephone hotlines, and survivor shelters had low utilization rates. Among all transgender participants, IPV survivors were significantly less likely than nonsurvivors to perceive family, medical doctors, and survivor hotlines as helpful HGRs for other survivors in general. Finally, transgender survivors were significantly less likely than nonsurvivors to self-report a willingness to disclose any future IPV to family. Although replication with larger, probability samples is needed, these findings suggest that friends often represent the primary line of defense for transgender survivors seeking help, and thus bystander intervention trainings and education should be adapted to address not just cisgender but also transgender IPV. Furthermore, because most formal HGR types appear to be underutilized and perceived more negatively by transgender survivors, renewed efforts are needed to tailor services, service advertising, and provider trainings to the needs of transgender communities. Directions for future research are reviewed.